Field Study of Riparian Zone along Sarawak River at Bintawa, Kuching - Mah, D.Y.S.; Pui, Allan P.P. (Universiti Malaysia Sarawak (UNIMAS), 2015)
Natural riparian zones are increasingly valued in recent years as they provide a variety of beneficial functions to the environment and possess substantial economic value. In this regard, it is necessary to call for simultaneous protection of the environment and promotion of economic growth. In this writing, a field methodology is presented for the purpose of riparian wetland conservation; it is used to investigate the riparian health through studying vegetation cover, human activities and groundwater table. Healthy riparian zones can be achieved through the balancing of riverbank human activities with maintaining the functionality of wetlands, which can be done by assessing the groundwater level a nd the amount of lush vegetation. A functioning riparian zone is found with a mean of 12% human activities in the range of 0 to 17.86%, within an area along the water edge measuring 100 m x 100 m. It is only natural that the higher the percentage of the wetland vegetation that is flourishing, the more the riparian zone is functioning well.